Electronic level gauge support - CUI JIANXIN; WEI JINXI; ZOU ZHI; LIU XINLEI; ZHANG XIN (2024)
The utility model discloses an electronic level gauge support which comprises a mounting plate, the top of the mounting plate is rotatably connected with three threaded rings, the top ends of the three threaded rings are in threaded connection with threaded telescopic rods, the top ends of the three threaded telescopic rods are rotatably connected with horizontal plates, and the top of the mounting plate is provided with an adjusting mechanism. The adjusting mechanism comprises a mounting groove, a horizontal ruler, fixing rods, a top plate, a rubber head and a crank, the mounting groove is formed in the top of the horizontal plate, the horizontal ruler is fixedly mounted on the inner wall of the mounting groove, and the outer ring of the mounting plate is rotationally connected with three fixing rods which penetrate through and extend into the mounting plate. The crank close to one side of the bubble is rotated to drive the fixing rod to rotate, the top plate is driven to do upward circular motion, the rubbe